3D Printed Meta‐Helmet for Wide‐Angle Thermal Camouflages. (25th May 2020) - Peng, Yu‐Gui; Li, Ying; Cao, Pei‐Chao; Zhu, Xue‐Feng; Qiu, Cheng‐Wei
Abstract: Thermal camouflage utilizes the manipulation of heat fluxes to conceal an arbitrary object in various environments from being detected via thermography. In the past decade, the field of thermal metamaterials and the technique of 3D printing have been rapidly developed, which makes nonintuitive heat flux manipulation feasible. However, when thermal metamaterials are applied to the thermal camouflaging, their conductivities are dependent on the properties of background, leading to the damage of background integrality. Moreover, previous thermal camouflaging schemes have mostly worked in the 2D regime, largely restricting their functional angles and application scenarios, especially in complex environments. Here, wide‐angle radiative thermal camouflaging is realized by using a 3D‐printed meta‐helmet of extremely anisotropic thermal conductivities. Based on 3D coordinate transformation, this meta‐helmet directly maps temperature distributions from the background to the metamaterial surface without damaging background integrity. The non‐invasive device is efficient in wide‐angle thermal camouflage by rendering the same emissivity to the background medium and can self‐adjust to various even unknown background thermal fields, which is demonstrated in numerical simulations and experiments. This work opens a door to the 3D transformation‐thermotics‐based devices for versatile practical applications in thermal infrared stealth of macro‐sized objects and others. Abstract : Based on transformation thermotics and 3D metal printing techniques, the authors experimentally demonstrate wide‐angle thermal camouflage. This non‐invasive radiative thermal camouflaging device is efficient in various unknown and/or time‐varying background thermal fields. It opens a door to the 3D transformation‐thermotics‐based devices for versatile practical applications, such as thermal infrared stealth of macro‐sized objects and others.